Factors associated with pregnancy-related anxiety among pregnant women attending antenatal care follow-up at Bedelle general hospital and Metu Karl comprehensive specialized hospital, Southwest Ethiopia - Tarafa, Hunde; Alemayehu, Yadeta; Nigussie, Meskerem (Frontiers in Psychiatry, 2022)
Pregnancy-related anxiety (PRA) is an anxiety related to the pregnancy, involving labor and delivery, the well-being of the fetus/infant and the mother, the availability of quality of healthcare resources, and the capacity to parent. There is scarcity of study conducted on magnitude of Pregnancy-related anxiety and its associated factors among pregnant women in Ethiopia. The main objective of this research was to assess factors associated with Pregnancy-related anxiety among pregnant women attending ANC follow-up at Bedelle general and Metu Karl comprehensive specialized hospitals, Southwest Ethiopia. A hospital-based cross-sectional study design was used among pregnant women attending ANC follow-up. Data were collected from 406 sampled pregnant women who were selected through a systematic random sampling technique. Pregnancy-Related Anxiety Questionnaire-Revised (PRAQ-R2) was used to measure the outcome variable. The collected data were analyzed using Statistical Package for Social Sciences (SPSS) version 26. Logistic regression analyses were done to identify factors associated with Pregnancy-related anxiety and significance level set at p < 0.05. The overall prevalence of PRA in this study was 32.7%. Unwanted pregnancy AOR = 2.77, 95% CI [1.71, 4.54], high perceived stress AOR = 2.39, 95% CI [1.54, 3.62], young age AOR = 2.14, 95% CI [1.49, 2.83], depression AOR = 2.09, 95% CI [1.39, 2.89], low income AOR = 2.01, 95% CI [1.29, 3.14], and poor social support AOR = 1.79, 95% CI [1.14, 3.37] were significantly associated with Pregnancy-related anxiety. The findings of this study showed that the prevalence of Pregnancy-related anxiety was high in the study area and positively associated with young age, low income, poor social support, high perceived stress, depression, and unwanted pregnancy. This finding suggests that clinicians should integrate screening for Pregnancy-related anxiety into clinical standards, more efforts should be made in the future to reduce the anxiety among pregnant women who had an unwanted pregnancy, young women, and poor social support. Also, it is good to encourage the pregnant mother to enhance their social connectedness by creating a self-help group, and increasing early identification of mental health problems throughout their daily ANC follow-up.